Cymbella gravida sp. nov. a new lacustrine taxon from Santa Cruz, Argentina - Maidana, Nora Irene (2013)
This study presents a detailed morphological analysis using light and scanning electron microscopy of Cymbella gravida sp. nov. collected from the deep sediments of Laguna Potrok Aike, a maar lake in the province of Santa Cruz, Argentina. An attempt was made to describe its ecological preferences based on the diatom assemblages present in the sections where C. gravida was found. This newly proposed species is compared with two morphologically related taxa, C. terrafuegiana Krammer and C. cistula var. guarrerae Ferrario, both described from the same locality in Tierra del Fuego. Light and scanning electron microscope observations of the original material allowed the establishment of their correct taxonomy.